Facing The Dangers in Indonesia’s Waters: Government’s Efforts in Proposing Illegal, Unreported and Unregulated Fishing as Transnational Organized Crime - Elyta Elyta; Dadang I.K. Mujiono; Uni W. Sagena (Intermestic: Journal of International Studies, 2022)
This study aims to understand and analyze the efforts made by the Government of Indonesia in proposing of Illegal, Unreported, And Unregulated Fishing( IUUF) as a Trans-National Organized Crime (TOC). The perspective used in this article is a realist perspective with a descriptive analysis method. The results of this study found that the Indonesian government's efforts to propose IUUF as a Trans-National Organized Crime (TOC), namely by suggesting and proposing IUUF as international law, as well as being the basis for punishing and prosecuting IUUF perpetrators, President Widodo has also shown his seriousness in eradicating IUFF, namely promoting IUUF to become a TOC has also been recognized internationally. Other government efforts have been to find agreement on the steps taken by Indonesia in controlling and protecting all-natural resources as maritime security in the IUUF case as one of the challenges of the nation, the Indonesian government ensures its citizens to manage natural resources to face internal and external threats external. Keywords: illegal, unreported, and unregulated fishing, Maritime Security, trans-national organized crime